The pupillary light response reflects eye-movement preparation - Mathôt, Sebastiaan; van der Linden, Lotje; Grainger, Jonathan; Vitu, Françoise (PeerJ PrePrints, 2014)
When the eyes are exposed to an increased influx of light, the pupils constrict. The pupillary light response (PLR) is traditionally believed to be purely reflexive and not susceptible to cognitive influences. In contrast to this traditional view, we report here that preparation of a PLR occurs in parallel with preparation of a saccadic eye movement towards a bright (or dark) stimulus, even before the eyes set in motion. Participants fixated a central gray area and made a saccade towards a peripheral target. Using gaze-contingent display changes, we manipulated whether or not the brightness of the target background was the same during and after saccade preparation. More specifically, on some trials we changed the brightness of the target background as soon as the eyes set in motion, thus dissociating the preparatory PLR (i.e. to the brightness of the target background before the saccade) from the 'regular' PLR (i.e. to the brightness after the saccade). We show that a PLR to the brightness of the to-be-fixated target background is prepared before the eyes set in motion. This reduces the latency of the PLR by approximately 100 ms. We link our findings to the pre-saccadic shift of attention: The pupil prepares to adjusts its size to the brightness of a to-be-fixated stimulus as soon as attention covertly shifts towards that stimulus, about 100 ms before a saccade is executed. Our findings illustrate that the PLR is a dynamic movement that is tightly linked to visual attention and eye-movement preparation.
Keywords: pupillomtery; eye movements; saccade preparation; visual attention; visual perception